Management of the System of Physical Education and Sports of Romania: Regulatory Foundaition (1948–1989) - Zavhorodnia, Tetiana; Tsybaniuk, Oleksandra (Pedagogical Discourse, 2016)
The article analyzed the content of professional laws and regulations fourth period of physical education and sport in Romania – the communist regime – 1948-1989 years. The initial stages singled official recognition of physical education and sports a priority in the development of the statein articles of the Constitution of the Romanian People’s Republic. Designated documents that regulate aspects of the system of physical culture and sports of the population of Romania. Specifically, the decree number 329/6 August 1949 on the establishment of the Committee for Physical Culture and Sports, the decision of the Council of Ministers of the country on July 2, 1957 a Union for Physical Culture and Sports. Serious attention is paid to the position of one of the most powerful laws of the study period from 29 December 1967 for the development of physical education and sport, which for 20 years regulate all aspects of the system call, including management. The central governing body recognized by the National Council for Physical Education and Sport, which is directed and coordinated the activities of physical education and sport. The author singled out the distribution of responsibilities and organization of physical mass sports activities among the population of Romania ministries and other government organizations (trade unions, the Communist Youth Union and the National Council of the Pioneer organization, Ministries of education and training, national defense and internal affairs, tourism and health care I, the National Union of industrial and agricultural cooperatives, the National Union of cooperatives of artisans and other government agencies). Key words: Romania, physical education, sports, National Council, the governing body, institutions, cooperation, ministry position.